"ENTENDES O QUE LÊS?": A NEUROCIÊNCIA E A INFLUÊNCIA DA TECNOLOGIA EM PROCESSOS DE LEITURA E INTERPRETAÇÃO DE TEXTOS EM CONCURSOS PÚBLICOS - Arruda, Janaina Rosa (2023)
How do we become readers? This is a question that has been part of my research for 10 years. As a Portuguese Language and Writing teacher for public service exams, this is a subject that has always sparked my interest and attention. Considering the individuality of each person, we know that this formation can be influenced by a variety of factors, starting with family, school, and affinity groups. There is no standard; there are stories behind each person. For this reason, the motivating questions for this study are: Can we continue to form ourselves as readers as adults? Can we refine our reading competence? This research focuses on a specific aspect within the vast universe of reading. It is an experiment that seeks to make use of knowledge from neuroscience and its relationship with technology (in devices and applications) for reading purposes. A significant contribution to this research from neuroscience comes from the studies conducted by Stalislas Dehaene in the book "The Neuronal Basis of Reading" and the contributions of Eric R. Kandel in "Principles of Neuroscience." Furthermore, scientific contributions from theories associated with the teaching practice of researcher Maryanne Wolf in her work "Reader, Come Home: The Reading Brain in a Digital World," which establishes a connection between reading and technology, also underpin the research. Regarding the experimentation that will be part of this observation, John H. Flavell's metacognition theory also contributes to reflections on its relationship with reading and interpretation. Therefore, the general objective is to establish points of convergence between reading and technology in classes taught on digital platforms. The intended specific objective is to observe the performance of public service exam candidates based on reading classes focused on neuroscience and metacognition conducted in cyberspace.